2020
DOI: 10.1016/j.yhbeh.2020.104757
|View full text |Cite
|
Sign up to set email alerts
|

Distributed physiology and the molecular basis of social life in eusocial insects

Abstract: The traditional focus of physiological and functional genomic research is on molecular processes that play out within a single body. In contrast, when social interactions occur, molecular and behavioral responses in interacting individuals can lead to physiological processes that are distributed across multiple individuals. In eusocial insect colonies, such multi-body processes are tightly integrated, involving social communication mechanisms that regulate the physiology of colony members. As a result, conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 216 publications
(276 reference statements)
1
30
0
Order By: Relevance
“…Besides different levels of relatedness, complex eusocial societies can be compared to simple multicellular organisms. Recently it has been suggested that social anatomy, referring to colonies being composed of specialized individuals, and social physiology, the set of mechanisms that coordinate the activity and the development of specialized individuals, (Friedmann et al 2020) parallel anatomy and physiology of multicellular organisms. Thus, the study of caste-specific aging and its underlying mechanisms may shed light on the evolution of aging patterns in early metazoans and on tissue-specific aging in advanced metazoans such as ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…Besides different levels of relatedness, complex eusocial societies can be compared to simple multicellular organisms. Recently it has been suggested that social anatomy, referring to colonies being composed of specialized individuals, and social physiology, the set of mechanisms that coordinate the activity and the development of specialized individuals, (Friedmann et al 2020) parallel anatomy and physiology of multicellular organisms. Thus, the study of caste-specific aging and its underlying mechanisms may shed light on the evolution of aging patterns in early metazoans and on tissue-specific aging in advanced metazoans such as ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…While most previous work has focused almost exclusively on gene expression, this research shows that for species that engage in trophallaxis, expression studies are necessary but insufficient to understand where in the colony the relevant genes are having their effects. It is conceivable that proteins produced in certain individuals could be sequestered by other individuals, allowing transmission of critical materials across superorganismal tissues (Friedman et al, 2020). In this view, proteins that exert effects in different individuals than the individuals that have produced them can be considered superorganismal hormones.…”
Section: Priorities For Resource Use As Colonies Maturementioning
confidence: 99%
“…As a result of the web of social interactions and social interdependency of individuals within social insect colonies, the molecular mechanisms underlying the expression of social behaviorand other traitsin social insect colonies are likely much more complex, involving genes and pathways distributed across multiple interacting individuals, when compared to the traits of solitary organisms that are at least less influenced by interactions with conspecifics [4,13]. Furthermore, genetic variation in the genomes of both the individual expressing the trait and her/his social partners (i.e., through direct or indirect genetic effects, respectively) may contribute to trait variation for individual-level traits, as well as for colony-level traits.…”
Section: The Genetic Basis Of Social Behavior Is Especially Complexmentioning
confidence: 99%